THE ROLE OF MATHEMATICS IN IMPROVING FINANCIAL LITERACY IN SCHOOL STUDENTS - Mingboyeva, Yulduz (Журнал математики и информатики, 2023)
This article discusses the special place and characteristics of financial literacy in the spirituality of a person in mathematics classes. In the article, the knowledge about the formation of financial knowledge and culture is revealed to students in mathematics classes. In order to improve students' financial literacy, examples from school mathematics are given.